1999
DOI: 10.1091/mbc.10.5.1445
|View full text |Cite
|
Sign up to set email alerts
|

Osmotically Induced Cell Volume Changes Alter Anterograde and Retrograde Transport, Golgi Structure, and COPI Dissociation

Abstract: Physiological conditions that impinge on constitutive traffic and affect organelle structure are not known. We report that osmotically induced cell volume changes, which are known to occur under a variety of conditions, rapidly inhibited endoplasmic reticulum (ER)-to-Golgi transport in mammalian cells. Both ER export and ER Golgi intermediate compartment (ERGIC)-to-Golgi trafficking steps were blocked, but retrograde transport was active, and it mediated ERGIC and Golgi collapse into the ER. Extensive tubulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
60
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 66 publications
3
60
0
Order By: Relevance
“…In this regard, our group's recent observations that overexpression of gK severely inhibited virion morphogenesis and intracellular trafficking of gK by collapsing Golgi into the ER (26) may be due to the lack of sufficient amounts of UL20p to transport gK from the ER to cell surfaces and TGN. The accumulation of gK within the ER, due to its inability to be transported to subsequent compartments, could mediate a cellular ER stress response and subsequent Golgi collapse (15,47). Additional biochemical experiments are needed to more accurately define gK/UL20p stoichiometric relationships and test whether these two proteins directly interact.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our group's recent observations that overexpression of gK severely inhibited virion morphogenesis and intracellular trafficking of gK by collapsing Golgi into the ER (26) may be due to the lack of sufficient amounts of UL20p to transport gK from the ER to cell surfaces and TGN. The accumulation of gK within the ER, due to its inability to be transported to subsequent compartments, could mediate a cellular ER stress response and subsequent Golgi collapse (15,47). Additional biochemical experiments are needed to more accurately define gK/UL20p stoichiometric relationships and test whether these two proteins directly interact.…”
Section: Discussionmentioning
confidence: 99%
“…Together with the partial resistance of the cis-Golgi to BFA after cargo receptor silencing, the lack of tubules implies that cargo receptors are required for efficient tubulation. The role of cargo receptors in promoting tubulation of the cis-Golgi indicated by GM130 was assessed by subjecting cells depleted of cargo receptors to hypotonic stress known to cause tubulation of the Golgi (Lee and Linstedt, 1999). Cells depleted of Surf4/ERGIC-53 or p25 showed no tubulation of the cis-Golgi, whereas in control cells the cis-Golgi was extensively tubulated after hypotonic stress (Figure 10).…”
Section: Silencing Of Surf4 and Ergic-53 Or P25 Dissociates Cop Imentioning
confidence: 99%
“…Membrane trafficking is a major process affected by hypertonicity that probably contributes significantly to the change incurred upon challenge. Indeed, we and others have observed that endocytosis, exocytosis, and vesicular trafficking are reduced from the onset of challenge, and that the reduction can persist hours after challenge (14)(15)(16)(17)(18)(19). However, how immediate changes in the cell's biophysical parameters influence these events is unclear.…”
mentioning
confidence: 93%